2021
DOI: 10.1183/23120541.00692-2020
|View full text |Cite
|
Sign up to set email alerts
|

Self-proning in COVID-19 patients on low-flow oxygen therapy: a cluster randomised controlled trial

Abstract: Rationale and objectivesProne positioning as a complement to oxygen therapy to treat hypoxemia in coronavirus disease (COVID-19) pneumonia in spontaneously breathing patients has been widely adopted, despite a lack of evidence for its benefit.To test the hypothesis that a simple incentive to self-prone for a maximum of 12 h per day would decrease oxygen needs in patients admitted to the ward for COVID-19 pneumonia on low-flow oxygen therapy.MethodsTwenty-seven patients with confirmed COVID-19 pneumonia admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 22 publications
0
76
0
5
Order By: Relevance
“…All published studies (randomized controlled trials (RCTs) and observational studies) that compared APP versus the control group in non-intubated COVID-19 subjects and reported one of the following outcomes: endotracheal intubation, mortality, and length of hospital stay were eligible for inclusion. All the studies that did not report endotracheal intubation or mortality rates were excluded, such as a study by Kharat et al 8 Only adult subjects aged 18 years or older were eligible for inclusion. We excluded single-arm studies, case reports, reviews, commentaries, preprints (not peer-reviewed), and abstracts.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…All published studies (randomized controlled trials (RCTs) and observational studies) that compared APP versus the control group in non-intubated COVID-19 subjects and reported one of the following outcomes: endotracheal intubation, mortality, and length of hospital stay were eligible for inclusion. All the studies that did not report endotracheal intubation or mortality rates were excluded, such as a study by Kharat et al 8 Only adult subjects aged 18 years or older were eligible for inclusion. We excluded single-arm studies, case reports, reviews, commentaries, preprints (not peer-reviewed), and abstracts.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Another retrospective, multicenter observational study included 827 non-intubated patients with COVID-19 and found that awake prone positioning (APP) was significantly associated with lower mortality (20.0% vs 37.9%; p < 0.0001) and intubation rate (23.6% vs 40.4%; p < 0.0001) as compared to supine position [8]. Randomized controlled trials have been done to evaluate the feasibility of implementation and patient compliance with APP in patients with COVID-19, but no long-term outcomes were assessed [9][10][11][12][13]. A recent systematic review found that APP improved oxygenation among patients with AHRF due to COVID-19, however, APP did not reduce intubation rates [14].…”
Section: Introductionmentioning
confidence: 99%
“…Out of all the articles, six studies have evaluated awake PP used outside the ICU for COVID-19 pneumonia. 6 , 7 , 10 , 14 , 19 , 22 Caputo et al applied PP to 50 COVID-19 patients in the Emergency Department and showed a significant improvement in oxygenation. 6 A one-day cross-sectional, beforeafter study was conducted by Sartini et al on 15 awake non-ICU patients on noninvasive ventilation (NIV) irrespective of the day.…”
Section: Resultsmentioning
confidence: 99%
“… 30 In addition, only a few studies have utilized control group for the evaluation of awake PP. 13 , 18 , 19 In all these studies, the assessment for improved oxygenation was undertaken as early as 1 hour 13 , 18 till the end of day one. 19 These studies’ results highlighting the improvement in oxygenation following such a short duration of awake PP could possibly be implicated to the transient lung recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation